(untitled) - Pempel, T. J. (Ithaca, N.Y., 1998)
Regime Shift suggests that Japan's present troubles are deeply rooted in the economy's earlier success. It is a much-anticipated work that offers an original framework for understanding the critical changes that have affected political and economic institutions in Japan.
Keywords: Economic history; 1945-